Load Propagation Balancing Strategy for Wireless Sensor Networks - Idris Afzal Shah; Mushtaq Ahmed (Tehnički Glasnik)
In this paper, we present a simplistic approach for many-to-one energy hole issue in Wireless Sensor Network (WSN) by load factoring sensor nodes. Load factor is a measure of link count i.e. the number of nodes a recipient node receives data from. We consider a strip-like distribution of nodes where leaf nodes have a load factor of zero as they only sense the surroundings while the factor count grows steadily as the data progress towards the root of the tree (base station). We present an “early load sharing” intervention strategy where a node spawns child process (in upward direction towards sink) for load balancing. Under network saturation, the node switches to advanced mode and transmit directly to Base Station/sink (BS) with residual energy. Extensive simulations demonstrate the effectiveness of proposed strategy.